Relación entre la recaudación tributaria y las importaciones de la región Loreto, periodo 2018 – 2022 - Isuiza Del Aguila, Reyna Isabel (2024)
The purpose of this thesis is to determine the relationship between tax collection and imports in Loreto, in the years 2018 to 2022, using a nonexperimental correlational design, analyzing tax collection, basically made up of two groups of taxes: Internal and Customs. From the analysis of the “Internal Taxes”, the tax that contributes the most to the collection is the “Income Tax” which, in the aforementioned period of analysis, amounted to the amount of S/ 1,080,702.3 million, representing 54.63% of the total, then There is “Production and Consumption Tax” with an amount of S/ 318,277.1 thousand, which represents 16.09% of the total, and, finally, there is “Other Income” with an amount of S/ 254,508.3 thousand, equivalent to 12.87%. of the total. The collection from “Customs Taxes” was S/ 324,598.9 thousand (16.41% of the total), with the greatest relevance in regional imports being “Raw Materials and Inputs” with an amount of S/ 427,935.18 thousand, equivalent to 82.85% of the total. The second item with the greatest contribution was “Capital Assets” with an amount of S/ 54,832.92 thousand (10.62% of the total). Concluding that there is no relationship between tax collection and imports in Loreto from 2018 to 2022, since the Pearson coefficient was 0.668793173, far from 1; Likewise, the coefficient of Determination (R2 ) = 0.447284308, less than 0.70, thus indicating that imports do not determine the trajectory of tax collection in Loreto.